The national PTA talks to parents how to get the best education for your child - Cutright, Melitta J. (Doubleday, 1989)
Topics covered include PTAs, preschool, sex stereotyping, kindergartens, report cards, parent-teacher conferences, standardized tests, homework, child care, AIDS in schools, sex education, drug abuse prevention, school reform, censorship.